Behavior under vague standards: Evidence from the laboratory - Sven Hoeppner; Laura Lyhs (Friedrich Schiller University Jena, 2016)
Doctrinal lawyers strive to reduce legal uncertainty based on the premise that difficult to predict legal consequences discourage socially desirable activities. Contributions from the economic theory of law suggest that increasing legal uncertainty can be socially beneficial. We test in an innovative laboratory experiment whether increasing the variability of an exogenous choice threshold (legal standard) increases or reduces socially desirable behavior. The results indicate a U-shaped relationship between increases in variability and activity choices: increases in variability first induce lower than optimal choices under an efficient standard (overcompliance), but eventually lead to greater than optimal choices under an efficient standard (undercompliance). We also find that overcompliance arises only under low degrees of standard variability. Moreover, increasing variability gradually crowds-out compliant choices. Finally, in the experiment minimal variability of the legal standard induces erratic individual behavior beyond socially satisfactory levels such that the standard loses its coordination function.
Keywords: C91; D02; K10; 330; legal uncertainty; vague legal standard; overcompliance and undercompliance; experimental law and economics; compliance crowding-out